Urgensi Masuknya Lembaga Penegak Hukum sebagai Oversigh dan Accountability Committee Danantara - Zacilasi Wasia; Zulkifli Andrian (Pusat Riset dan Inovasi Nasional, 2025)
The debate surrounding the inclusion of law enforcement agencies in the structure of Danantara has become a hotly debated discourse among the public because it is considered an attempt to minimize the duties and authority of law enforcement agencies in conducting oversight. Based on a review of the concept of separation of powers and the principle of checks and balances and the concept of COI, it can be said that the inclusion of law enforcement agencies in the structure of Danantara does not have a clear urgency because in fact, without being included as Danantara's oversight and accountability committee, the police and the prosecutor's office as law enforcement agencies should be able to carry out their duties properly in terms of overseeing Danantara. In fact, being involved in Danantara will further dwarf the functions of the police and prosecutor's office because they are easily involved in organizational conflicts of interest, which has become a disease of this nation. The inclusion of the prosecutor's office and the police as oversight and accountability committees also oversteps the legal instruments that provide the legal umbrella for the existence of these two institutions. The inclusion of law enforcement agencies in Danantara's structure could also create an imbalance of power. The government argues as if the inclusion of the police and prosecutor's office as Danantara's oversight and accountability committees strengthens the commitment to accountable and transparent management of state assets and maintains balance and control over Danantara.